THE ROLE OF CREATINE IN NEUROLOGICAL DISORDERS: A LITERATURE REVIEW - Amin Omidi; Maja Ćwiek; Klaudia Malec; Bartosz Krawiec; Bartłomiej Zarębski; Olaf Jadanowski; Jakub Sójka; Maksymilian Szombara; Michał Mokrzyński; Piotr Szyszka (International Journal of Innovative Technologies in Social Science, 2025)
Creatine, widely known as a performance-enhancing supplement for athletes and bodybuilders is increasingly recognized for its potential neuroprotective properties. Beyond its well-established role in energy metabolism and muscle physiology, creatine appears to influence brain function by supporting ATP homeostasis, reducing oxidative stress, and stabilizing neuronal membranes. Recent studies have suggested that creatine supplementation may benefit individuals with neurodegenerative disorders such as Parkinson’s disease, Huntington’s disease, amyotrophic lateral sclerosis (ALS) and Alzheimer’s disease. Additionally, preliminary findings indicate a potential role for creatine in mitigating the effects of acute brain injuries and mood disorders, including major depressive disorder. Despite promising experimental data, the clinical efficacy of creatine in neurological settings remains under investigation, with inconsistent results across human trials. This review aims to summarize current knowledge on the neuroprotective effects of creatine and critically assess the quality of available evidence.